Science Student– Teacher’s Reflection Upon Intelleectual and Procedural Honesty on Conducted Practicals - PACHAURY, A.C. (SCHOOL SCIENCE, 2006)
Science for all up to secondary stage was envisaged making future citizens literate and endowed with scientific temper. Teaching of the prescribed scientific content and remembering it by the students neither develops nor nurtures scientific outlook and attitude in them. Proper understanding and appreciation of scientific concepts can only come by engaging learners in processes and procedures that unearth unknown characteristics possessed by the physical, chemical or biological realities that they can investigate at their level of cognitive functioning.